Ocean citizenship behavior sebagai variabel mediasi antara leader mindset dan kinerja karyawan di industri maritim - Sururi, Muhammad; Rahayu, Sri; Fitrianty, Rifda (Nur Science Institute, 2025)
This study aims to comprehensively analyze the influence of leader mindset on ocean citizenship behavior and its implications on employee performance in the maritime sector, using the Structural Equation Modeling-Partial Least Squares approach. This approach was chosen for its ability to analyze complex structural models with latent variables and multidimensional causal relationships to explore how sustainability-oriented leadership mindsets and maritime ethics can drive pro-environmental and pro-social behaviors among employees. The results of the study showed that Leader Mindset had a positive and significant effect on OCB, Leader Mindset had a positive and significant effect on employee performance, OCB had a positive and significant effect on employee performance, and OCB was proven to mediate the relationship between Leader Mindset and employee performance. These findings confirm that visionary, innovative, and maritime ecosystem-conscious leadership encourages employee marine citizenship behaviors, which ultimately improve individual and organizational performance, so that the development of a leadership mindset and the formation of OCBs are important strategies to increase the effectiveness of maritime organizations.